Rancang Bangun Smart Cashier System Berbasis Web dengan Fitur Point Of Sale (POS) dan Manajemen Transaksi Real-Time sebagai Solusi Digitalisasi Koperasi pada Kantor Imigrasi Kelas I TPI Jambi - M. Yusuf; Nur Apnhi Alamsyah Putri; Alisya Rahayu; Winda Utama; Dwi Lestari; Juliana, Windy Tri; Ferdinand Ali; Pardi Yansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Digital transformation is essential for improving the effectiveness and efficiency of organizational data management and service delivery. The employee cooperative at the Immigration Office Class I TPI Jambi still relies on semi-manual transaction management, causing recording delays, calculation errors, and difficulties in producing timely and accurate reports. This study aims to design and develop a web-based Smart Cashier System with Point of Sale (POS) and real-time transaction management features to support cooperative digitalization. The system was developed using the Waterfall model, covering requirement analysis, system design, implementation, testing, and maintenance. Its novelty lies in integrating POS, Role-Based Access Control (RBAC), a payment gateway, real-time inventory updates, and automated reporting within a single web-based cooperative information system. The results show that the system successfully integrates product management, sales transactions, inventory control, and automated reporting. Black Box Testing conducted on 10 functional scenarios produced a 100% success rate, with all scenarios achieving PASS status. These findings confirm that the system meets the specified functional requirements. Its implementation is expected to improve operational efficiency, accelerate transaction processing, enhance data accuracy, and support the cooperative’s digital transformation.